Pendampingan Dan Konsultasi Manajemen Bisnis Dan Keuangan UMKM Dengan Digitalisasi Industry 4.o - Zulfa Zakiatul Hidayah; Erin Soleha; Fiqih Maria Rabiatul Hariroh; Muhamad Syahwildan; Isarianto Isarianto (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Knowledge of finance plays a very important role in the sustainability of a business, from the main aspects of business finance and management knowledge are always the main foundation. As times progress, especially in the era of digitalization, it is very unfortunate when business people pay less attention to financial aspects and optimizing business management. Financial management can be carried out when the Human Resources in the business have the competence to adapt to current developments in the 4.o industry. Moved from a living environment where business actors have very little education regarding finances and how to manage a business so that it can grow and adapt to digital developments as well as the lack of education and training provided for business actors, especially micro businesses, in this community service activity We aim to provide assistance and consultation to business actors in Bumi Citra Lestari Housing which is expected to start from one business actor and expand to other business actors. This service activity is designed to focus more on providing business assistance starting from business management to finance, so as to provide maximum results with the competence of the human resources they have, especially for business actors who have high competitiveness in this era of digitalization so that in the future they can optimize all business activities in order to improve profits and sales as well so that the business can survive for a long time and continue to grow.